Motorcycle rider error and engagement in distracting activities: A study using the Attention-Related Driving Errors Scale (ARDES-M) - Ledesma, Ruben Daniel (2023)
Research on motorcycle rider distraction and inattention is limited, especially when compared to that on car drivers. This study examines motorcycle rider error and its relationship with engagement in distracting activities. Additionally, it provides an adaptation of the Attention-Related Driving Errors Scale for use with motorcycle riders (ARDES-M). A sample of 418 motorcyclists responded to a web questionnaire consisting of the ARDES-M, a self-report measure of Involvement in Distracting Activities (IDA), a measure of everyday inattention (ARCES, Attention Related Cognitive Errors Scale) and socio-demographic and riding-related questions. Riding errors were associated with a higher level of engagement in distracting activities and a greater propensity for inattention in daily life. ARDES-M scores were associated with various types of self-reported traffic crashes and near-crashes, while self-reported distractions (IDA) were only linked with near-crashes. The most widely self-reported distracting activities were using map navigation, listening to the radio or to music and adjusting vehicle devices. The various uses of cell phones were relatively minor. Young riders reported higher levels of engagement in distracting activities and committing more riding errors. The ARDES-M showed good psychometric properties for the sample in Spain.